Structural basis for catalysis by human lipoyl synthase - Olga A. Esakova; Douglas M. Warui; Syam Sundar Neti; John N. Alumasa; Squire J. Booker (Nature Communications)
Abstract Lipoic acid is an essential cofactor in five mitochondrial multiprotein complexes. In each complex, it is tethered in an amide linkage to the side chain of a conserved lysyl residue on a lipoyl carrier protein or lipoyl domain to afford the lipoyl cofactor. Lipoyl synthase catalyzes the last step in the biosynthesis of the lipoyl cofactor, the addition of two sulfur atoms to carbons 6 and 8 of an octanoyllysyl residue of the H protein, the lipoyl carrier protein of the glycine cleavage system. Lipoyl synthase, a member of the radical S-adenosylmethionine superfamily, contains two [Fe4S4] clusters, one of which is sacrificed during catalysis to supply the appended sulfur atoms. Herein, we use X-ray crystallography to characterize several stages in lipoyl synthase catalysis and present a structure of an intermediate wherein the enzyme is cross-linked to the H protein substrate through a 6-mercaptooctanoyl ligand to a [Fe3S4] cluster.